Adjustment experiences and coping strategies of first-year students at the University of Limpopo (Turfloop Campus) - Tom, Reyagalaletsa Felicity (University of Limpopo, 2015)
First year at university is challenging. For most students adjustment to social and academic life entails a degree of stress and emotional difficulties. These difficulties can result in a greater risk of first year attrition. The study sought to understand and describe the adjustment experiences of a sample of first year students at the University of Limpopo (Turfloop Campus). Qualitative research was conducted to establish the lived experiences of the participants. Four focus groups were conducted, in all there were eighteen first year participants from different departments. Data were gathered by use of semi-structured interviews which allowed probing. Thematic Content Analysis was employed to glean themes from the data. The study concluded that some of the first year participants struggled to adjust to social and academic life at the institution. This was exacerbated by the presence of insufficient support from university personnel, financial problems, unmanageable workloads, and unfamiliar method of instruction. These participants tended to use negative coping mechanism such as ignoring problems, smoking marijuana and propositioning the opposite sex (males). However, some of the participants had positive adjustment experiences and used positive coping mechanisms such as working hard, interacting with lecturing staff, listening to music, interacting with peers and attending religious events. The study recommended that orientation for first year students should incorporate a programme that helped first year students understand the challenges they are likely to face.
Thesis (M.A.( Psychology)) --University of Limpopo, 2015
Keywords: Adjustment; Coping strategies; First-year students; Adjustment (Psychology); Universities and Colleges -- Students; Clinical Psychology